2010
DOI: 10.1007/s10549-010-1218-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the androgen estrogen conversion pathway in relation to breast cancer prognosticators

Abstract: Purpose:Genetic variation in the androgen-to-estrogen conversion pathway has been shown to be associated with risk of breast cancer, and in particular with Estrogen Receptor (ER) positive tumours. We aimed at studying how the genetic alterations, which have been identified for risk, are associated with breast cancer prognosticators, with a prior hypothesis that, in general, hormone related breast cancers have a better prognosis than non-hormone related breast cancers. Methods:Association between tagging SNPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Since AI response may be dependent on the CYP19A1 SNP rs4646 (Colomer et al , 2008; Darabi et al , 2011), the rs4646 allele distribution was assessed. The rs4646 distribution did not significantly differ between groups A and B (results not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AI response may be dependent on the CYP19A1 SNP rs4646 (Colomer et al , 2008; Darabi et al , 2011), the rs4646 allele distribution was assessed. The rs4646 distribution did not significantly differ between groups A and B (results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, adjuvant AI treatment had no effect on breast cancer-free survival in this group of patients, a finding suggestive of AI resistance. Therefore, we analysed the allele distribution of the CYP19A1 rs4646, which has been suggested to be involved in AI resistance (Colomer et al , 2008; Darabi et al , 2011). The difference in AI and TAM treatment response in group B was independent of the CYP19A1 rs4646 variant.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies about polymorphisms in linkage disequilibrium with rs10046 which describe a significant association with efficacy of the aromatase inhibitor letrozole in patients with breast cancer, as is the case for rs700158 [42] and rs4646 [23], [24]. The latter SNP has also been reported to be associated with HER2 status of tumors [9], circulating steroid hormones [35] and histological grade and tumor size in postmenopausal women [35], [43]. Haiman et al reported a significant relationship between this SNP and circulating estrogen levels among postmenopausal women.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, rs10046 has been related to altered disease free survival in the subgroup of pre-menopausal breast cancer patients [9]. Polymorphisms in linkage disequilibrium with rs10046, as in the case of rs4664, rs700518 and rs700519, has been associated with variable efficacy of treatments [23], [24], [42] and breast cancer survival [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…The p value for the Cochran-Armitage trend test of association (with 21 breast cancer risk) for this SNP was 0.008 in our study [12] . We recently found this SNP to also be associated with both tumour grade and tumour size amongst the cases in CAHRES [20] , with p values of 0.002 and 0.030, based on fitting an ordinal logistic model and a linear regression model, respectively.…”
Section: A Genetic Association Analysis Of Breast Cancer Based On Genmentioning
confidence: 99%